The Integration of Adult Acute Care Surgeons into Pediatric Surgical Care Models Supplements the Workforce without Compromising Quality of Care. Issue 9 (September 2015) - Judhan, Rudy J.; Silhy, Raquel; Statler, Kristen; Khan, Mija; Dyer, Benjamin; Thompson, Stephanie; Richmond, Bryan
Acute care of children remains a challenge due to a shortage of pediatric surgeons, particularly in rural areas. In our institutional norm, all cases in patients age six and older are managed by dedicated general surgeons. The provision of care to these children by these surgeons alleviates the impact of such shortages. We conducted a five-year retrospective analysis of all acute care pediatric surgical cases performed in patients aged 6 to 17 years by a dedicated group of adult general surgeons in a rural tertiary care hospital. Demographics, procedure, complications, outcomes, length of stay, and time of consultation/operation were obtained via chart review. Elective, trauma related, or procedures performed by a pediatric surgeon were excluded. Descriptive statistics are reported. A total of 397 cases were performed by six dedicated general surgeons during the study period. Mean age was 11.5 ± 3.1 years. In all, 100 (25.2%) were transferred from outlying facilities and 52.6 per cent of consultations/operations occurred at night (7P–7A), of which 33.2 per cent occurred during late night hours (11P–7A). On weekends, 34.0 per cent occurred. Appendectomy was the most commonly performed operation (n = 357, 89.9%), of which 311 were laparoscopic (87.1%). Others included incision/drainage (4.5%), laparoscopic cholecystectomy (2.0%), bowel resection (1.5%), incarcerated hernia (0.5%), small bowel obstruction (0.5%), intraabdominal abscess drainage (0.3%), resection of intussusception (0.3%), Graham patch (0.3%), and resection omental torsion (0.3%). Median length of stay was two days. Complications occurred in 23 patients (5.8%), of which 22(5.5%) were the result of the disease process. These results parallel those published by pediatric surgeons in this age group and for the diagnoses treated. Models integrating dedicated general surgeons into pediatric call rotations can be designed such that quality of pediatric care is maintained while providing relief to an overburdened pediatric surgical workforce.